Efektifitas Job Satisfaction Dalam Meningkatkan Kinerja Karyawan Pada Divisi Business, Government Dan Enterprise Services PT Telkom Witel Medan - Sidauruk, Evita Paula; Simanjorang, Feronica (Talenta Publisher, 2024)
This study aims to analyse the effect of job satisfaction on employee performance at the Business, Government and Enterprise Services Division of PT Telkom Witel Medan. This is motivated by the decline in Telkom's performance as seen from the decline in Indihome Market Share in the last three years. In this case, employee performance can be influenced by many factors, one of which is job satisfaction. When doing their job, positive support directly or indirectly from the company has an impact on the work produced by individuals. So that in fulfilling the required quality, the company provides positive support to support employee satisfaction at work. This research uses a qualitative research method with a descriptive approach. The primary data collection of this research is by conducting interviews and direct observation at the BGES Division of PT Telkom Witel Medan. Then secondary data is obtained from related literature studies. The results showed that job satisfaction has a great influence on improving employee performance in the BGES Division of PT Telkom Witel Medan such as increasing productivity. The results also show that job satisfaction is very effective in influencing employee loyalty to the company.